Transfusion of female blood in a rat model is associated with red blood cells entrapment in organs - Alshalani, Abdulrahman; de Wissel, Marit B.; Tuip-de Boer, Anita M.; Roelofs, Joris J. T. H.; van Bruggen, Robin; Acker, Jason P.; Juffermans, Nicole P. (PloS one, 2023)
Transfusion of red blood cells (RBCs) has been associated with adverse outcomes. Mechanisms may be related to donor sex and biological age of RBC. This study hypothesized that receipt of female blood is associated with decreased post-transfusion recovery (PTR) and a concomitant increased organ entrapment in rats, related to young age of donor RBCs. Donor rats underwent bloodletting to stimulate production of new, young RBCs, followed by Percoll fractionation for further enrichment of young RBCs based on their low density. Control donors did not undergo these procedures. Male rats received either a (biotinylated) standard RBC product or a product enriched for young RBCs, derived from either male or female donors. Controls received saline. Organs and blood samples were harvested after 24 hours. This study found no difference in PTR between groups, although only the group receiving young RBCs from females failed to reach a PTR of 75%. Receipt of both standard RBCs and young RBCs from females was associated with increased entrapment of donor RBCs in the lung, liver, and spleen compared to receiving blood from male donors. Soluble ICAM-1 and markers of hemolysis were higher in recipients of female blood compared to control. In conclusion, transfusing RBCs from female donors, but not from male donors, is associated with trapping of donor RBCs in organs, accompanied by endothelial activation and hemolysis.